2009
DOI: 10.1192/apt.bp.107.005207
|View full text |Cite
|
Sign up to set email alerts
|

The postgraduate curriculum and assessment programme in psychiatry: the underlying principles

Abstract: SuMMARyAssessment is key to the educational process and plays a significant role in looking at the progress trainees make as a result of training and personal development. Recent developments in curricula have led to substantial changes in assessing progress and attainment throughout postgraduate medical education in the UK. This article outlines the framework used to develop the postgraduate curriculum in psychiatry and describes the nature and purpose of the assessment programme that forms part of this new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Firstly, the test content should be planned in relation to the learning outcomes by the process of blueprinting. A blueprint is a matrix in which the test designer decides how many items/tasks are to be assessed for each subject or category (Holsgrove et al, 2009). Secondly, the blueprinting should also ensure that the format of an assessment is appropriate for the domain (such as knowledge, skills or attitudes) of the curriculum that it intends to assess (Wass et al, 2001).…”
Section: Curriculum Development and Blueprintingmentioning
confidence: 99%
“…Firstly, the test content should be planned in relation to the learning outcomes by the process of blueprinting. A blueprint is a matrix in which the test designer decides how many items/tasks are to be assessed for each subject or category (Holsgrove et al, 2009). Secondly, the blueprinting should also ensure that the format of an assessment is appropriate for the domain (such as knowledge, skills or attitudes) of the curriculum that it intends to assess (Wass et al, 2001).…”
Section: Curriculum Development and Blueprintingmentioning
confidence: 99%
“…27 We have found that mini-PATs have consistently low response rates from multidisciplinary team members. Allowing core trainees to nominate assessors from previous posts within the last year may help to resolve some of these difficulties.…”
Section: Wpbas and Psychiatric Trainingmentioning
confidence: 99%
“…10 Assessors 37 are less likely to correctly administer a tool that significantly limits their freedom to employ their professional judgement. 27 Although the current WPBA forms do allow for some 'free text' comments by assessors, they remain secondary to lists of Likert-scale scores, limiting the opportunity for trainees to gain specific advice on how to improve their performance. Workplace-based assessments must provide relevant feedback to trainees, 4 which is a powerful instrument in furthering their personal and professional development.…”
Section: Assessment Of Psychiatric Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…[182223] The most up to date and comprehensive entry requirements for each paper are given in Table 2.…”
Section: Introductionmentioning
confidence: 99%